2018
DOI: 10.1038/s41598-018-29082-6
|View full text |Cite
|
Sign up to set email alerts
|

Propolis potentiates the effect of cranberry (Vaccinium macrocarpon) against the virulence of uropathogenic Escherichia coli

Abstract: Uropathogenic Escherichia coli (UPEC), the most prevalent bacteria isolated in urinary tract infections (UTI), is now frequently resistant to antibiotics used to treat this pathology. The antibacterial properties of cranberry and propolis could reduce the frequency of UTIs and thus the use of antibiotics, helping in the fight against the emergence of antibiotic resistance. Transcriptomic profiles of a clinical UPEC strain exposed to cranberry proanthocyanidins alone (190 µg/mL), propolis alone (102.4 µg/mL) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…Propolis has antimicrobial, anti-inflammatory, anti-tumoral, immunemodulatory and anti-oxidant activities (Boonsai et al, 2014). It has been used for several years to treat gastrointestinal disorders (food supplement) (Freitas et al, 2006), to promote oral health (mouthwash) (Pereira et al, 2011) and in dermatological care (creams and ointments) (Olczyk et al, 2014;Pasupuleti et al, 2017;Ranfaing et al, 2018b). In vitro studies showed that propolis potentiated the effect of cranberry proanthocyanidins on adhesion, motility (swarming and swimming), biofilm formation (early formation and fully-formed biofilm), iron metabolism and stress response of UPEC (Olczyk et al, 2014;Pasupuleti et al, 2017;Ranfaing et al, 2018a,b).…”
Section: Cranberry (Vaccinium Macrocarpon)mentioning
confidence: 99%
See 1 more Smart Citation
“…Propolis has antimicrobial, anti-inflammatory, anti-tumoral, immunemodulatory and anti-oxidant activities (Boonsai et al, 2014). It has been used for several years to treat gastrointestinal disorders (food supplement) (Freitas et al, 2006), to promote oral health (mouthwash) (Pereira et al, 2011) and in dermatological care (creams and ointments) (Olczyk et al, 2014;Pasupuleti et al, 2017;Ranfaing et al, 2018b). In vitro studies showed that propolis potentiated the effect of cranberry proanthocyanidins on adhesion, motility (swarming and swimming), biofilm formation (early formation and fully-formed biofilm), iron metabolism and stress response of UPEC (Olczyk et al, 2014;Pasupuleti et al, 2017;Ranfaing et al, 2018a,b).…”
Section: Cranberry (Vaccinium Macrocarpon)mentioning
confidence: 99%
“…It has been used for several years to treat gastrointestinal disorders (food supplement) ( Freitas et al, 2006 ), to promote oral health (mouthwash) ( Pereira et al, 2011 ) and in dermatological care (creams and ointments) ( Olczyk et al, 2014 ; Pasupuleti et al, 2017 ; Ranfaing et al, 2018b ). In vitro studies showed that propolis potentiated the effect of cranberry proanthocyanidins on adhesion, motility (swarming and swimming), biofilm formation (early formation and fully-formed biofilm), iron metabolism and stress response of UPEC ( Olczyk et al, 2014 ; Pasupuleti et al, 2017 ; Ranfaing et al, 2018a , b ). Moreover, this association was active in all the E. coli strains studied, ruling out the variable effect observed with the cranberry used alone ( Ranfaing et al, 2018a ).…”
Section: Nutraceuticalsmentioning
confidence: 99%
“…In vivo studies proved that cranberry proanthocyanidins (190 μg/ml) have a relationship to adhesion, motility, biofilm formation, and iron and stress response of uropathogenic Escherichia coli. Furthermore, cranberry proanthocyanidins influence the transcriptional profiles of Escherichia coli, anti-adhesion effect is mainly the effect of proanthocyanidins on “strategic” genes involved in E. coli adherence [85].…”
Section: Biological Activities Of European Cranberrymentioning
confidence: 99%
“…Accordingly, the condensed tannins of cranberry extracts most commonly known as proanthocyanidins (cPACs) has been reported to reduce the hydrophobicity of bacterial cell surfaces and interfere with their attachment to host cellular or biomaterial surfaces [45]. A similar anti-motility trend was also observed with cranberry pomace extracts against Enterococcus faecalis , Escherichia coli , Pseudomonas aeruginosa and Proteus mirabilis [4547].…”
Section: Discussionmentioning
confidence: 95%